Making friends : the art of social networking in life and online - Meyer, Jared (New York : Rosen Pub., 2012)
Explores in the importance of friendships, using social networks, meeting new people, and building and maintaining lasting friendships.
Friendship basics -- Social networking : online and offline -- Developing new contacts -- Maintaining your friendships -- Building lifelong relationships.
Includes bibliographical references (p. 70-77) and index.
Young Adult.
Young Adult
Keywords: Friendship -- Juvenile literature; Online social networks -- Juvenile literature; Friendship; Online social networks; Friendship; Social networking